Functional analysis of T and B cells from blood and thyroid tissue in Hashimoto's disease. - McLachlan, S M (1985)
B lymphocytes from Hashimoto blood and thyroid tissue have been cultured with autologous T cells from thyroid/blood to assess their ability to synthesise IgG and thyroid autoantibody. Thyroid B cells were able to synthesize microsomal antibody spontaneously in the absence of T cells or pokeweed mitogen (PWM) and this synthesis was increased in the presence of thyroid T cells without PWM or with blood T cells with PWM. In contrast, blood B cells did not secrete thyroid autoantibody spontaneously but could be induced to do so by thyroid T cells spontaneously or by blood T cells with PWM. Despite these differences, lymphocytes from blood and thyroid tissue secreted microsomal or thyroglobulin antibodies in culture which were similar in terms of the IgG subclass distribution. It would appear, therefore, that although the state of activation of B and T cells is different in blood and thyroid tissue, the precursors of thyroid autoantibody secreting cells are the same.